2016
DOI: 10.1038/nmat4566
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization switching by spin–orbit torque in an antiferromagnet–ferromagnet bilayer system

Abstract: Spin-orbit torque (SOT)-Electrical manipulation of magnetization allows us to realize low-power and high-performance solid-state devices. Recent studies have revealed that an in-plane electric current applied to a heterostructure with large spin-orbit interaction and structural inversion asymmetry gives rise to a torque, so-called SOT, which in turn induces a magnetization switching [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . The SOT-induced switching is useful for three-terminal spintron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
637
4
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 883 publications
(658 citation statements)
references
References 36 publications
13
637
4
4
Order By: Relevance
“…This has been predicted theoretically [32][33][34] and experimentally observed [32,[35][36][37]. It was also recently demonstrated that both collinear [38] and non-collinear AFMs [33,[39][40][41][42] can generate a large SOT on FMs in AFM/FM heterostructures. While the origin of such a torque is not clear [41] it is known that in heavy metal/FM heterostructures, the SHE plays an important role [43,44].…”
supporting
confidence: 54%
“…This has been predicted theoretically [32][33][34] and experimentally observed [32,[35][36][37]. It was also recently demonstrated that both collinear [38] and non-collinear AFMs [33,[39][40][41][42] can generate a large SOT on FMs in AFM/FM heterostructures. While the origin of such a torque is not clear [41] it is known that in heavy metal/FM heterostructures, the SHE plays an important role [43,44].…”
supporting
confidence: 54%
“…b Data for Fe 50 Rh 50 are for the specific antiferromagnetic-to-ferromagnetic transition. Fukami et al, 2016;Lau et al, 2016;Oh et al, 2016) (see Sec. III.D.4)].…”
Section: Metalmentioning
confidence: 99%
“…38 It has been experimentally demonstrated that antiferromagnets with strong spin-orbit coupling can also act as efficient SHE spin injectors. Measurements showing electrical reorientation of a ferromagnet by the SHE induced in an adjacent antiferromagnet 59,60 highlight that antiferromagnetic spintronics aims not only at replacing ferromagnets but also at assisting ferromagnets in their performance in spintronic devices. We also note that, according to recent theory predictions, 61 even insulating antiferromagnets can act as efficient spin-current sources via the antiferromagnetic resonance spin pumping.…”
Section: Generation Detection and Transmission Of Spin-currents In mentioning
confidence: 99%
“…In previous sections we already mentioned examples of metal antiferromagnets which have so far driven much of the research in antiferromagnetic spintronics. Alloys of Ir and Mn are a prime example of metal antiferromagnets gradually progressing from favorable passive exchange-bias materials to active electrodes in TAMR devices, 8,16,17,19 to SHE injectors of spin current controlling adjacent ferromagnets, 59,60 or to sensitive spin detectors.…”
mentioning
confidence: 99%